Analysis of Cultural Differences in Dubai. - Reiser, Danina (Unternehmensführung und Unternehmensrecht - Band 6., 2011)
Hauptbeschreibung Over the years Dubai has become a cultural melting pot as people go there pursuing career and prosperity. To work and live in such an inhomogeneous environment can be very challenging due to different cultural expectations and values. Only if these differences are acknowledged for what they are, people will coexist harmoniously. This thesis aims to find out how people with different nationalities and cultures are able to adapt to a new culturally-blended environment, to which extent they are willing to compromise or change their way of thinking and which parts of their cultur.